Enhancing the Interfacial Adhesion of a Ductile Gold Electrode with PDMS Using an Interlocking Structure for Applications in Temperature Sensors - Shuai Shi; Penghao Zhao; Pan Yang; Le Zhao; Jingguang Yi; Zuohui Wang; Shihui Yu (Nanomaterials, 2025)
The poor interfacial adhesion between ductile gold (Au) electrodes and polydimethylsiloxane (PDMS) substrates affects their application in flexible sensors. Here, a porous Au electrode is designed and combined with a flexible PDMS substrate to form a structure that embeds Au into the PDMS film, thereby enhancing the interfacial adhesion of the Au/PDMS electrode. The resistivity change of the Au/PDMS electrode is only 12.3% after 100 tape peeling trials. The resistance of the Au/PDMS electrode remains stable at the 30% strain level after 2000 tensile cycling tests. This feature is mainly attributed to the deformation buffering effect of the porous Au film. After 100 min of ultrasonic oscillation testing, the resistivity change of the Au/PDMS electrode remains stable. It is also shown that the Au/PDMS electrode has excellent interfacial adhesion properties, which is mainly attributed to the interlocking effect of the Au/PDMS electrode structure. In addition, the temperature coefficient of resistance (TCR) of the temperature sensor based on the Au/PDMS electrode is approximately 0.00320/°C and the sensor’s sensitivity remains almost stable after 200 temperature measurement cycles. Au/PDMS electrodes have great potential for a wide range of applications in flexible electronics due to their excellent interfacial adhesion and electrical stability.